A killing of innocents : a novel [large type] - Crombie, Deborah (Crombie, Deborah. Duncan Kincaid & Gemma James ;, 2023)
Trainee doctor Sasha Johnson hurries through the crowd in London's historic Russell Square. Someone jostles her as they brush past. A moment later, Sasha stumbles, then collapses. When detectives Duncan Kincaid and Doug Cullen are called to the scene, they discover that she's been stabbed. Kincaid immediately calls his detective wife, Gemma Jones, who is on the task force for knife crimes. Along with Gemma's partner, the team works to unravel the case. When the killer strikes again, even friendships are put on the line to find them before panic spreads across London. -- adapted from back cover